"It was Pretty Scary": The Theme of Fear in Young Adult Women's Descriptions of a History of Adolescent Dating Abuse. (1st November 2013) - Burton, Candace W.; Halpern-Felsher, Bonnie; Rehm, Roberta S.; Rankin, Sally; Humphreys, Janice C.
<x xml:space="preserve">Abstract</x> The mental health impact of abusive adolescent dating relationships has not been well described, but fear related to abuse has been reported. We elaborate the theme of fear in women's descriptions of a history of adolescent dating abuse. A sample of community-based women, ages 19–34, who experienced an abusive dating relationship during adolescence (ages 11–20) was used. Data were analyzed via thematic analysis. Fear was a consistent and resonant theme. Three types of fear were identified: fear for self, fear for other relationships, and fearful expectation. These results offer important insights into the impact of abusive adolescent relationships on women's mental health.